Being white in the new South Africa : the experience of a group of young Afrikaners - Duncan, Norman (University of Pretoria, 2018)
This study aimed at uncovering what it means to be white within the context of post- Apartheid South Africa through examining the perceptions, beliefs, and experiences held by a group of young Afrikaners (the first democratic Afrikaner generation or 1DAGs). Framed within the social constructionist paradigm, this study employed Critical Discourse Analysis as overall methodological framework for analysing participants’ discourses. In contributing to the development and refinement of appropriate and effective methodological procedures for the generation of quality rich data, the study employed “hanging out,” a conventional sociological data gathering methodology, also adapting this procedure to an online version, i.e. “hanging out online”. Seven discursive themes emerged from participants’ accounts, which fundamentally served to describe: (i) perceptions of the current South African social formation and the associated position of the Afrikaner (whites) and the “other,” (ii) perceptions of the ways in which the majority ruling party utilise their position(s) of political power, (iii) the threats 1DAGs experience, and (iv) the impact of their subjective beliefs and associated experiences on their self and group-based perceptions. Deeper critical engagement with these texts revealed possible contradictions and oppositions within the data, which have exposed the potential for alternative meanings or interpretations to emerge. Findings from this investigation indicate that, for this particular group, whiteness in post-Apartheid South Africa is perceived as a burden, and that being white in the new South Africa relates to being oppressed and having to manoeuvre and manage such oppressive conditions in order to have space to strive for a meaningful existence.